Anti-atherogenic effect of Channa striatus fish extract in high cholesterol-fed rabbits - Hakim, Muhammad Nazrul; Yee, Pang Chong; Cheema, Manraj Singh; Keong, Yong Yoke; Ahmad, Zuraini (University of Benin, 2024)
Purpose: To determine the effect of aqueous extract of Channa striatus on plasma lipids concentrations, pro-inflammatory cytokines levels, adhesion molecules and arterial plaque formation in cholesterol-fed rabbits. Methods: New Zealand rabbits (n = 30, females) were divided into five groups of six rabbits each as follows: cholesterol control group (0.5 % cholesterol); normal control group (normal diet), positive control group (0.5 % cholesterol + 5 mg/kg atorvastatin); and treatment groups (0.5% cholesterol + 250 mg/kg or 500 mg/kg C. striatus extracts, respectively) for 6 weeks. Blood was taken every 2 weeks and analyzed for total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), triglyceride (TG), tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β). Atherogenic index (AI) was calculated based on LDL:HDL ratio. Results: Cholesterol feeding for 6 weeks resulted in significantly increased TC, LDL, HDL, AI, TG, TNF-α and IL-1β when compared to C. striatus-fed rabbits. Serum LDL was 26.34 ± 1.43 mmol/L in C. striatus group to 30.52 ± 0.82 mmol/L in cholesterol group (p < 0.05). C. striatus extract (250 mg/kg) increased HDL by approximately 400 % (6.23 ± 1.76 mmol/L from 0.72 ± 0.18 mmol/L), decreased AI value (4.6 in C. striatus group to 10.4 in cholesterol group). Also, IL-1β and TNF-α concentration also significantly (p < 0.05) reduced with C. striatus administration. Interestingly, down-regulation of ICAM-1 and VCAM-1 expression and reduced plaque formation were observed with C. striatus feeding. Conclusion: Channa striatus extract is effective in reducing atherogenesis. This could be due to the high HDL level produced in 250 mg/kg dose group, and strongly suggests the significance of HDL in preventing atherogenesis even if other lipid profiles remain unchanged.